Analysis of Organizational Culture, Job Satisfaction and Leadership Style on Employee Performance with Organizational Commitment as an Intervening Variable - Harnadi; Suyanto; Indri Astuti (GoodWill, 2025)
This study investigates the impact of organizational culture, job satisfaction, and leadership style on employee performance, with organizational commitment as a mediating variable at PT. Smart Elang Felindo. Motivated by the company’s need to enhance employee performance, the research emphasizes strengthening organizational commitment as a key strategy. Using a quantitative method and Structural Equation Modeling with SmartPLS, data were collected from 92 employees with at least three years of service, selected through proportionate stratified random sampling. Questionnaires assessed organizational culture, job satisfaction, leadership style, commitment, and performance, with performance evaluations completed by branch heads to ensure objectivity. The findings reveal that organizational culture, job satisfaction, and leadership style significantly and positively influence organizational commitment, which in turn significantly affects employee performance. Furthermore, these three variables also indirectly impact performance through organizational commitment. The study highlights the strategic role of commitment in translating internal organizational factors into improved employee outcomes. By involving experienced employees and using 18 measurement indicators, the study offers practical recommendations for human resource management to enhance sustainable performance.